Development of utilization of electrical lamp for fixed lift net (bagan) in Makassar Strait. (April 2019) - Sudirman; Najamuddin; Palo, M; Musbir; Kurnia, M; Nelwan, A
Abstract: The use of light in some types of fisheries has been one of the most advanced and successful methods to control fish for capture purposes. The use of electrical lamps has been developed as a method of attracting small pelagic fish in Indonesia. Fixed lift nets ( bagan tancap ) are a fishing gear type categorized as lift nets with fine meshed (0.5 cm mesh size) box-shaped netting, operated using lamps to attract pelagic fish. Several studies on fixed lift nets ( bagan ) were conducted in Makassar Strait, South Sulawesi, Indonesia from 2012-2017. These studies used various types of electric lamps, such as halogen lamps, mercury lamps, incandescent lamps and light emitting diodes (LEDs). The fishing process was analysed through on-board observation during fishing operations and interviews with fixed lift net fishermen. The results showed that small pelagic fish species tended to prefer the halogen (neon) lamps compare to mercury and incandescent lamps, as they were more effective in attracting small pelagic species to fixed lift nets in the coastal area. A new type of lamp considered more environmentally friendly, the light emitting diode (LED), was also introduced on fixed lift nets. The result of the research on introducing light emitting diodes (LEDs) in fixed lift nets is discussed.